Artificial Intelligence (AI) in academic research. A multi-group analysis of students’ awareness and perceptions using gender and programme type (Journal of Applied Learning and Teaching, 2024)
The era of AI has brought tremendous impact in academic research, and this has provided the impetus for students to leverage on novel tools in carrying out a lot of quality research works. Previous studies have relied so much on AI for instruction, classroom management and assessment and utilisation of AI tools for research has scarcely been examined. This study covered the gap by examining students’ utilisation of AI tools based on their level of awareness and perception and finding out the difference based on gender and programme type in such prediction. A total of 5554 university students were used for the study. Exploratory factor analysis was first carried for dimensionality and other validity checks (convergent and discriminant) using Average Variance Extracted (AVE) and Fornel-Larcker criterion and methods. Population t-tests and multi-group analyses were performed using SPSS and Smart PLS 3. The study found that students have high level of awareness and positive perception of AI tools in research. Similarly, the level of utilisation of AI tools in research is high. Male and postgraduate students have a higher level of awareness and positive perception of AI tools in research, with female students stronger than male students in terms. Perception and awareness directly impacted on utilisation but perception mediates positively and significantly in the nexus between awareness and utilisation. The study findings provide useful insights into using AI tools among university students and also identify the rationale to consider variables like gender and programme type when developing curriculum that will meet the current technology needs in our higher institutions.